PENGARUH MEDIA SOSIAL TERHADAP PERSEPSI REMAJA TENTANG KESETARAAN GENDER - Nasriyah, Nasriyah (Center for Gender and Children Studies, Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) UIN Sultan Thaha Saifuddin Jambi, 2023)
This study examines the influence of social media on adolescents' perception of gender equality. Through qualitative methods that include in-depth interviews, observations, and documentation analysis, the study reveals how social media content, social interactions, and influencer roles shape adolescent views. The findings show that social media has great potential in educating and raising awareness about gender equality. However, biased information and unhealthy debates can also hinder adolescents' understanding. The implications of this study emphasize the importance of digital literacy among adolescents and the responsibility of influencers in promoting gender equality values. Recommendations are given to improve media literacy and provide appropriate guidance for adolescents in filtering information on social media